Kolaborasi Antara Model Dan Pendekatan Saintifik Oleh Guru Biologi Di SMA Kecamatan Kuta Baro - Dini Askia Safitri; Zamzami Zamzami; Silvi Puspa Widya Lubis (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to assess the ability of teachers to apply models and scientific approaches to learning. This type of research is quantitative research with descriptive methods. The population to be studied in this study is the teachers of SMA Se, Kuta Baro District. The sample in this study were biology teachers. The results of the questionnaire in this study showed that the learning model score had an average value of 87%, which is the very good category; and the scientific approach score had an average value of 86%, which is the very good category. The conclusion of this study is that biology teachers at SMA Se, Kuta Baro District, have been able to collaborate on scientific models, and approaches